Two new species of soldier beetles (Coleoptera, Cantharidae), the first from the tribe Silini in Dominican amber - Fanti, Fabrizio; Pankowski, Maximilian G. (Zootaxa, 2021)
The Silinae is the most frequently observed subfamily of soldier beetles (Insecta, Coleoptera, Cantharidae) living today in Hispaniola (the Dominican Republic and Haiti). This subfamily also was recently found in Dominican amber with the discovery of the genus Tytthonyx (Silinae, Tytthonyxini). Here we describe and illustrate two new species of this subfamily—the first representatives of the tribe Silini and genus Silis in Dominican amber. Silis (s. str.) hegnai sp. nov. and Silis (s. str.) curleri sp. nov. are easily distinguishable from extinct species of Silis as well as those living in Hispaniola today.